2020
DOI: 10.3892/ol.2020.11857
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and safety of apatinib monotherapy in the treatment of patients with advanced epithelial ovarian carcinoma who progressed after standard regimens and the analysis of the VEGFR2 polymorphism

Abstract: The aims of the present study were to investigate the clinical outcomes and safety of apatinib monotherapy in the treatment of patients with advanced epithelial ovarian carcinoma (EOC) who have progressed after standard regimens, and to analyze the vascular endothelial growth factor receptor 2 (VEGFR2) rs2071559 polymorphism. A total of 118 patients with advanced EOC who received apatinib treatment were included in the study. Tumor response was evaluated using progression-free survival (PFS) and overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Additionally, another study initiated by Yan and colleagues performed the association analysis between VEGFR2 gene polymorphism and efficacy of apatinib in the treatment of advanced epithelial ovarian carcinoma. 39 Results of their study indicated that the clinical outcomes of apatinib may be influenced by the polymorphism -906T>C of VEGFR2 through mediating the mRNA expression of VEGFR2 . In conclusion, these data demonstrated the potential predictive significance of polymorphism in antiangiogenic single pathway for the efficacy and prognosis of patients receiving antiangiogenic targeted drugs therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another study initiated by Yan and colleagues performed the association analysis between VEGFR2 gene polymorphism and efficacy of apatinib in the treatment of advanced epithelial ovarian carcinoma. 39 Results of their study indicated that the clinical outcomes of apatinib may be influenced by the polymorphism -906T>C of VEGFR2 through mediating the mRNA expression of VEGFR2 . In conclusion, these data demonstrated the potential predictive significance of polymorphism in antiangiogenic single pathway for the efficacy and prognosis of patients receiving antiangiogenic targeted drugs therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study suggested that rs2071559 of VEGFR2 gene was of clinical significance to predict the efficacy in patients with epithelial ovarian carcinoma (EOC) treated with apatinib. 23 In conclusion, these data demonstrated the potential predictive value of KDR gene for efficacy in patients receiving apatinib treatment. However, no potential polymorphism biomarkers were available to predict the efficacy and safety of apatinib for patients with chemotherapy-refractory metastatic CRC.…”
Section: Introductionmentioning
confidence: 57%
“…The forward primer was 5ʹ-TCACTAGGGCTCTTCGTTGG-3ʹ, the reverse primer was 5ʹ-GAAGCGGATACTCAGCCAAG-3ʹ according to the previous study. 23 The size of the amplified products was 271 bp, a total of 2 μL amplified products were digested using the restriction enzyme BsmI (Thermo Fisher Scientific, USA). The genotypes of the polymorphism were distinguished through the size of PCR bands as follows: TT genotype (one 271 bp band); CC genotype (one 108 bp band and one 163 bp band); TC genotype (one 271 bp band, one 108 bp band and one 163 bp band).…”
Section: Methodsmentioning
confidence: 99%
“… 36 Interestingly, the multivariate Cox regression analysis for PFS in our study also found that FIGO stage and first-line platinum response might be independent factors to predict the PFS, which was in concert with the results in a previous retrospective study regarding apatinib in EOC. 37 …”
Section: Discussionmentioning
confidence: 99%